The Electronic Brand Experience Affecting Electronic Loyalty among Generation Y Consumers: The Mediating Role of Electronic Satisfaction - Prabpailin, Areeya; Watcharacharoen, Nipunnama; Plangthin, Pawanrat; Poomidin, Parichat; Dansiri, Warapon (MBA-KKU Journal, 2023)
This study aims to investigate the impact of electronic brand experience on electronic loyalty, the influence of electronic satisfaction on electronic loyalty, and the consumer behavior regarding electronic brand experiences among Generation Y individuals in the digital tourism platform industry. The research employed a quantitative method, and a questionnaire, which served as a primary research tool, was rigorously tested for reliability and content validity. Data were collected from 400 respondents from Generation Z, aged between 23 and 43, all of whom had previous experience with digital travel platforms. Hypotheses were tested using multiple linear regression and path analysis. The results indicated a positive relationship between Electronic Brand Experience and Electronic Satisfaction, as well as a positive relationship between Electronic Satisfaction and Electronic Lolalty. Furthermore, this study also examined the direct and indirect effects of Electronic Brand Experience on Electronic Loyalty when Electronic Satisfaction serves as the intermediating variable. The study’s results indicated that the intermediating variable exerts a partial influence on Electronic Loyalty, thus confirming the hypotheses. This study contributes significantly to our understanding of electronic brand experiences in the digital travel platform business, benefiting both academic and managerial applications. It provides valuable insights for enhancing strategies within the tourism industry and fostering its growth.”